BS ISO 23551-11. Safety and control devices for gas burners and gas-burning appliances. Particular requirements. Part 11. Automatic shut-off valves for operating pressure of above 500 kPa up to and including 6300 kPa (18th February 2020) - British Standards Institution,
No abstract available